Glutathione-Sensitive Mesoporous Organosilica-Coated Gold Nanorods as Drug Delivery System for Photothermal Therapy-Enhanced Precise Chemotherapy - Song, Hui; Peng, Tingwei; Wang, Xue; Li, Beibei; Wang, Yufang; Song, Dianhai; Xu, Tianzhao; Liu, Xinghui (Frontiers in Chemistry, 2022)
The combination of photothermal therapy (PTT) and chemotherapy can remarkably improve the permeability of the cell membrane and reduce the concentration of chemotherapy agents that not only kill the tumor cells effectively but also have adverse effects on normal tissues. It is of great meaning to construct nanomaterials that could be simultaneously applied for tumor eradication with PTT and chemotherapy. In this work, we developed a novel gold nanorod coated with mesoporous organosilica nanoparticles (oMSN-GNR), which presented as an optimal photothermal contrast agent. Moreover, after doxorubicin loading (oMSN-GNR–DOX), the organosilica shell exhibited biodegradable properties under high glutathione in the tumor microenvironment, resulting in massively releasing doxorubicin to kill tumor cells. More importantly, the hyperthermia effect of GNR cores under near-infrared light provided promising opportunities for localized photothermal ablation in vivo. Therefore, the combination of precise chemotherapy and highly effective PTT successfully inhibited tumor growth in liver tumor-bearing mice. This versatile synergistic therapy with local heating and chemotherapeutics precise release opens up the potential clinical application of PTT and chemotherapy therapeutics for malignant tumor eradication.